Research and radiation monitoring of rocks in the quarry and finished products at the Gorodske granite and migmatite deposit to protect workers and prevent occupational diseases - A.O. Kryvoruchko; S.S. Iskov; O.L. Herasymchuk; O.V. Mushtaiev; K.O. Mushtaiev (Технічна інженерія, 2024)
The publication describes the procedure for research and radiation monitoring of rocks in the quarry and finished products at the Gorodske granite and migmatite deposit to protect workers and prevent occupational diseases. The paper presents a methodology for measuring and assessing the natural radioactivity of rocks in igneous rock deposits and a methodology for measuring the specific effective activity in a deposit, which is determined by the value of the total specific activity of natural radionuclides, which is defined as the weighted sum of the specific activity of radium-226, thorium-232, and potassium-40. The classification of mineral raw materials and groups of deposits by the degree of radioactivity is analyzed. The procedure for determining the dose rate of gamma radiation, measuring the equivalent dose rate of gamma radiation, and measuring the specific effective activity of natural radionuclides in rocks by the express method is presented. As a result of measurements, modeling, geometrization and research, models were obtained that determine the change in the specific equivalent dose of gamma radiation and specific activity of radionuclides within the field area under study. The main conclusions and recommendations for the development of the Gorodske deposit with regard to radiation control are presented.